A Contrast Based Calculation Method for Roadway Lighting. Issue 3 (3rd July 2018) - AbouElhamd, Amira R.; Saraiji, Riad
ABSTRACT: In this article, we present a new calculation procedure that is based on contrast of obstacles along the road. We have developed a methodology to calculate the contrast of obstacles from the perspective of the driver. Obstacles of various heights relative to the ground were distributed along the lateral and longitudinal directions of the road. Using three-dimensional vector analysis, we determined the location of the target's background as seen by the driver. The contrast values were then calculated along the length of the street for each obstacles' height. We show how various street lighting design variables such as pole spacing, pole height, lamp lumens, and car headlights affect the values of the target contrast along the street. The findings suggest that the contrast-based approach to street lighting design has merit and could be the basis for street lighting calculation in the future.